FEATURES OF JUSTICE AS AN OBJECT OF ADMINISTRATIVE-LEGAL REGULATION AND ENSURING LEGALITY (Bulletin of criminological association of Ukraine, 2023)
The article, based on the analysis of the scientific views of scientists, reveals general theoretical approaches to the interpretation of the concept of "administrative-legal regulation". The author's vision is proposed regarding the list of characteristic features of justice as an object of administrative-legal regulation and ensuring legality. It is argued that administrative-legal regulation of justice, through the prism of legality, is a purposeful activity of authorized entities to ensure the work of courts in accordance with the requirements of current procedural legislation (criminal, civil, administrative) to establish the rule of law, based on an objective and comprehensive analysis of factual circumstances and making reasoned decisions, relying on the hierarchical system of regulatory legal acts existing in the state. It is generalized that as an object of administrative and legal regulation, justice has the following features: 1) the presence of a special legal status and guarantees of activity for the subjects of justice administration, judges; 2) the delimitation of the powers of courts regarding the consideration of cases, that is, the presence of jurisdiction over cases; 3) impartial and fair decision-making based on the provisions of the Constitution of Ukraine and other legislative and subordinate legislation; 4) the binding nature of the adopted court decisions for execution by all subjects regardless of their origin (public or private subjects), forms of ownership, etc. Therefore, ensuring legality is an important goal and at the same time one of the necessary features of justice.
Keywords: administrative and legal regulation; justice; legality; courts; judges